Pole piece and electrochemical device comprising same
By arranging a composite lithium supplement material layer with gradient content on the current collector of the lithium-ion battery electrode sheet, the problem of degradation of battery circulation performance and gas production risks caused by the residual lithium supplement material is solved, and the uniform release of lithium and the improvement of battery safety is achieved.
Patent Information
- Application Number
- CN202311157367.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-07
- Publication Date
- 2025-03-07
AI Technical Summary
During the lithium replenishment process of existing lithium-ion batteries, lithium replenishment materials remain in the electrode sheet, hindering the transmission of ions and electrons, resulting in a degradation of battery circulation performance, and a potential gas production risk, affecting safety.
A pole sheet is designed, and an active material layer of composite lithium supplement material with gradient content is arranged on the current collector. By arranging multiple layers of composite lithium supplement material in the thickness direction of the pole sheet, the uniform release of lithium is ensured.
It significantly improves the circulating performance of the battery, reduces gas production problems and safety risks, and reduces the risk of lithium excretion.
Smart Images

Figure CN119581480A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and specifically provides a pole piece and an electrochemical device comprising the pole piece. Background Art
[0002] With the continuous rapid development of large-scale energy storage, electric vehicles, consumer electronics and other fields, the demand for lithium-ion batteries is also growing. Many performances such as energy density, fast charging capability, safety and reliability are getting closer and closer to the limit. This requires seeking new breakthroughs in technology, innovating chemical systems, battery cell structures, and manufacturing processes, and then realizing the continuous improvement of the comprehensive capabilities of the new generation of lithium-ion batteries. In particular, in order to improve the energy density of current high-energy-density power batteries, the pole piece lithium replenishment method has begun to be introduced. After releasing Li, the pole piece lithium replenishment material will remain in the pole piece, becoming a shackle that hinders the transmission of ions and electrons; in addition, due to the problem of poor kinetics when the lithium replenishment material releases Li, it is easy for the lithium replenishment material at different distances from the current collector in the pole piece to release Li to different degrees, which will bring about the hidden danger of continuous gas production in the subsequent cycle process, affecting the battery cycle performance, and the safety test pass will also be greatly reduced. Summary of the invention
[0003] In order to solve the above problems, the object of the present invention is to provide a pole piece, characterized in that the pole piece includes a current collector and an active material layer arranged on the current collector, the active material layer consists of a 1st layer to an Nth layer arranged in sequence in the thickness direction, N>1, and N is an integer, the 1st layer is adjacent to the current collector, and the Nth layer is the layer farthest from the current collector in the active material layer, and there are an i-th layer and an i+1-th layer in the 1st layer to the N-th layer, 1≤i≤N-1, and i is an integer,
[0004] The i-th layer and the i+1-th layer contain a composite lithium supplement material, and based on the total weight of the i-th layer, the content of the composite lithium supplement material in the i-th layer is C i Based on the total weight of the i+1th layer, the content of the composite lithium supplement material in the i+1th layer is C i+1 , and among them
[0005] C i >C i+1 , and Ci-C i+1 <8%.
[0006] By arranging an active material layer of a composite lithium replenishing material with a gradient content on the current collector of the pole piece, the active material layer farther from the current collector contains a lower content of the composite lithium replenishing material. During the lithium replenishment process, lithium can be released evenly without being affected by the distance from the current collector, which significantly improves the cycle performance of the battery and reduces the gas production problem and safety risks of the battery to a certain extent. In addition, setting a gradient content of the composite lithium replenishing material in the pole piece according to the present invention, especially the positive pole piece, can also reduce the risk of lithium precipitation.
[0007] According to one embodiment of the present invention, N is, for example, 2 to 50. In some embodiments, N is at least 2. In some embodiments, N is at least 3. In some embodiments, N is at least 4.
[0008] According to one embodiment of the present invention, the first to Nth layers have substantially the same thickness.
[0009] According to one embodiment of the present invention, the first to Nth layers have different thicknesses.
[0010] According to one embodiment of the present invention, the thickness of the i-th layer is less than 1 μm.
[0011] According to one embodiment of the present invention, the thickness of the i-th layer is 0.1μm to 2μm, for example, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm or any interval thereof.
[0012] According to one embodiment of the present invention, the i-th layer and the (i+1)-th layer contain the same type of composite lithium supplementing material.
[0013] According to one embodiment of the present invention, the composite lithium-replenishing materials in the i-th layer and the (i+1)-th layer are the same type of composite lithium-replenishing materials.
[0014] According to one embodiment of the present invention, the composite lithium supplement material includes a lithium supplement frame and a lithium supplement material.
[0015] According to one embodiment of the present invention, the lithium supplement frame is porous, and in particular, the lithium supplement frame is a honeycomb lithium supplement frame. In some embodiments, the lithium supplement material is loaded on the honeycomb lithium supplement frame.
[0016] According to one embodiment of the present invention, the lithium supplement framework includes at least one of the following: porous carbon, carbon nanotubes, carbon fibers, graphene, metal-organic framework compounds (MOFs), SnO2, ZnO, indium-doped tin oxide (ITO), antimony-doped tin oxide (ATO), and ruthenium oxide.
[0017] Conventional lithium supplement materials leave the remaining components in the pole piece after releasing lithium, thus negatively affecting the gram capacity of the pole piece. In contrast, in the present invention, since a honeycomb lithium supplement frame is used in the composite lithium supplement material, these composite lithium supplement materials only retain the lithium supplement frame that plays a positive role in the conductivity of the pole piece after releasing lithium. More advantageously, these retained lithium supplement frames are arranged in the active material layer in the same gradient as the electronic conductive agent, that is, the active material layer away from the current collector has fewer lithium supplement frames, while the active material layer close to the current collector has more lithium supplement frames and can bear more electron transmission pressure, which further optimizes the electronic transmission network of the battery and improves the kinetic performance of the battery.
[0018] According to one embodiment of the present invention, the pole piece is a positive pole piece, the current collector is a positive current collector, and the active material layer is a positive active material layer. In some embodiments, the composite lithium supplement material includes a lithium supplement frame and a positive lithium supplement material, and the positive lithium supplement material includes at least one of lithium halide, lithium sulfide, lithium oxide, lithium peroxide, lithium nitride, and Li2C2.
[0019] According to one embodiment of the present invention, the pole piece is a negative pole piece, the current collector is a negative current collector, and the active material layer is a negative active material layer. In some embodiments, the composite lithium supplement material includes a lithium supplement frame and a negative lithium supplement material, and the negative lithium supplement material includes at least one of metallic lithium and a lithium alloy, and the lithium alloy includes at least one of a lithium aluminum alloy and a lithium indium alloy.
[0020] According to one embodiment of the present invention, the porosity of the composite lithium supplement material is 20% to 70%, preferably 30% to 50%.
[0021] According to one embodiment of the present invention, the average particle size D1 of the composite lithium supplement material is 20nm-20μm, preferably 100nm-10μm. When the particle size of the composite lithium supplement material is too large, the specific surface area of the composite lithium supplement material is too small, and the electronic ion conduction network is degraded, so that the lithium supplement material cannot be fully released during the first charge; too small a particle size of the composite lithium supplement material will greatly increase the difficulty of preparing the slurry, causing slurry gel, agglomeration and other problems, thereby negatively affecting the processability of the pole piece.
[0022] According to one embodiment of the present invention, based on the total weight of the Nth layer, the content of the composite lithium supplement material in the Nth layer is C N, and 0.5 wt% ≤ C N <C i ≤10 wt%, preferably 2 wt%≤C N <C i ≤5 wt%. In some embodiments, C i 1 wt%, 2 wt%, 3 wt%, 4 wt%, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%. In some embodiments, C N The content is 0.5%, 1%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5% and 5.0% by weight.
[0023] According to one embodiment of the present invention, when i is any integer from 1 to N-1, it satisfies: 3.5×C i+1 >C i >C i+1 , preferably 2.5×C i+1 >C i >1.2×C i+1 In some embodiments, when i is any integer from 1 to N-1, 3.5×C i+1 >Ci>C i+1 , for example C i It can be 1.1C i+1 , 1.2C i+1 , 1.3C i+1 , 1.4C i+1 , 1.5C i+1 , 1.6C i+1 , 1.7C i+1 , 1.8C i+1 , 1.9C i+1 , 2.0C i+1 , 2.1C i+1 , 2.2C i+1 , 2.3C i+1 , 2.4C i+1 , 2.5C i+1 , 2.6C i+1 , 2.7C i+1 , 2.8C i+1 , 2.9C i+1 , 3.0C i+1 , 3.1C i+1 3.2C i+1 3.3C i+1 , 3.4C i+1 Or any interval composed of them, preferably 2.5×C i+1 >C i >1.2×C i+1As a result, the content gradient of the composite lithium supplement material between adjacent layers is smoothly transitioned, which avoids the structural instability caused by a large content difference between adjacent layers.
[0024] According to one embodiment of the present invention, there are an i-th layer and a j-th layer in the first layer to the N-th layer, 1≤i≤N-1, 1≤j≤N-1, i and j are both integers and i≠j, and based on the total weight of the j-th layer, the content of the composite lithium supplement material in the j-th layer is C j , and among them, |C i -C j |≤(|ij| / (N-1))*6%. Thus, the content difference of the composite lithium supplement material from the first layer to the Nth layer is kept within a certain range, ensuring the stability and consistency of the process of releasing lithium from the composite lithium supplement material. In some embodiments, |C i -C j |≤(|ij| / (N-1))*5.5%,|C i -C j |≤(|ij| / (N-1))*5%,|C i -C j |≤(|ij| / (N-1))*4.5%,|C i -C j |≤(|ij| / (N-1))*4%.
[0025] According to one embodiment of the present invention, the average particle size D2 of the lithium supplement material is 1 nm to 1 μm, preferably 5 nm to 0.5 μm. When the lithium supplement material particles are too large, their specific surface area is too small, which leads to a degraded electronic ion conduction network; when the lithium supplement material particles are too small, the lithium supplement material itself is extremely reactive, which may cause excessive consumption of additives in the electrolyte and decomposition of the electrolyte solvent, thereby undesirably affecting the performance of the battery cell and causing increased gas production.
[0026] According to one embodiment of the present invention, the average particle size D1 of the composite lithium supplement material and the average particle size D2 of the lithium supplement material satisfy: 5≤D1 / D2≤50, preferably 10≤D1 / D2≤20.
[0027] According to one embodiment of the present invention, based on the weight of the composite lithium-supplementing material, the content of the lithium-supplementing framework is 15 wt % to 55 wt %, preferably 25 wt % to 40 wt %.
[0028] According to one embodiment of the present invention, based on the weight of the composite lithium-supplementing material, the content of the lithium-supplementing material is 45 wt % to 85 wt %, preferably 60 wt % to 75 wt %.
[0029] The present invention also aims to provide an electrochemical device, wherein the electrochemical device comprises the pole piece according to the present invention. In some embodiments, the electrochemical device comprises the positive pole piece according to the present invention, in some embodiments, the electrochemical device comprises the negative pole piece according to the present invention, and in some embodiments, the electrochemical device comprises the positive pole piece and the negative pole piece according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to make the above-mentioned purpose, features and advantages of the present invention easier to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to fully understand the present invention, but the present invention can also be implemented in other ways different from those described herein, so the present invention is not limited to the specific embodiments disclosed below.
[0031] Figure 1 A cross-sectional view of a pole piece according to the present invention is schematically shown.
[0032] Figure 2 A cross-sectional view of a pole piece according to the present invention is schematically shown. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application. All other embodiments obtained by those skilled in the art based on the technical scheme provided by the present application and the embodiments given belong to the scope of protection of the present application.
[0034] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0035] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0036] Composite lithium supplement materials
[0037] According to some embodiments of the present application, the composite lithium supplement material includes a lithium supplement frame and a lithium supplement material.
[0038] In some embodiments, the lithium-replenishing framework includes at least one of the following: porous carbon, carbon nanotubes, carbon fibers, graphene, metal-organic framework compounds (MOFs), SnO2, ZnO, indium-doped tin oxide (ITO), antimony-doped tin oxide (ATO), and ruthenium oxide.
[0039] In some embodiments, the porosity of the composite lithium supplement material is 20% to 70%, preferably 30% to 50%, for example 30%, 35%, 40%, 45%, 50% or any interval thereof.
[0040] In some embodiments, the average particle size D1 of the composite lithium supplementing material is 20 nm-20 μm, preferably 100 nm-10 μm.
[0041] In some embodiments, the average particle size D2 of the lithium supplementing material is 1 nm-1 μm, preferably 5 nm-0.5 μm.
[0042] In some embodiments, the average particle size D1 of the composite lithium supplement material and the average particle size D2 of the lithium supplement material satisfy: 5≤D1 / D2≤50, preferably 10≤D1 / D2≤20.
[0043] In some embodiments, based on the weight of the composite lithium-supplementing material, the content of the lithium-supplementing framework is 15 wt % to 55 wt %, for example, 15 wt %, 20 wt %, 25 wt %, 30 wt %, 35 wt %, 40 wt %, 45 wt %, 50 wt %, 55 wt % or any range thereof, preferably 25 wt % to 40 wt %.
[0044] In some embodiments, based on the weight of the composite lithium-supplementing material, the content of the lithium-supplementing material is 45% to 85%, for example, 45 weight %, 50 weight %, 55 weight %, 60 weight %, 65 weight %, 70 weight %, 75 weight %, 80 weight %, 85 weight % or any range thereof, preferably 60 weight % to 75 weight %.
[0045] Electrochemical Devices
[0046] According to some embodiments of the present application, the electrochemical device includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The electrochemical device according to the present invention can be a secondary battery, such as a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.
[0047] According to some embodiments of the present application, the negative electrode plate is the negative electrode plate according to the present application, wherein the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer includes a negative electrode active material, a negative electrode composite lithium supplement material, a conductive agent and a binder.
[0048] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, the negative electrode active material layer consists of a 1st layer to an Nth layer arranged in sequence in the thickness direction, N>1, and N is an integer, the 1st layer is adjacent to the negative electrode current collector, and the Nth layer is the layer farthest from the negative electrode current collector in the negative electrode active material layer, and there are an i-th layer and an i+1-th layer in the 1st layer to the N-th layer, 1≤i≤N-1, and i is an integer,
[0049] The i-th layer and the i+1-th layer contain negative electrode composite lithium supplement materials, and based on the total weight of the i-th layer, the content of the negative electrode composite lithium supplement material in the i-th layer is C i Based on the total weight of the i+1th layer, the content of the negative electrode composite lithium supplement material in the i+1th layer is C i+1 , and among them
[0050] C i >C i+1 , and Ci-C i+1 <8%.
[0051] In some embodiments, the negative electrode active material may be a commonly used negative electrode active material, including but not limited to: graphite, carbon material, silicon-based material, metal oxide, tin-based material. For example, silicon-based composite materials include but are not limited to silicon-carbon composite materials, silicon-metal oxide composite materials, silicon alloy composite materials. For example, metal oxides include but are not limited to iron oxide, lithium titanate, copper oxide, etc., which are regarded as all metal oxides that can be used for lithium extraction and storage.
[0052] In some embodiments, the conductive agent can be a commonly used conductive agent, including but not limited to: metal-based materials, carbon-based materials, conductive polymers and mixtures thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, nickel, copper, aluminum or silver. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, acetylene black, Ketjen black, carbon black, carbon fiber or any combination thereof. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0053] In some embodiments, the binder can be a commonly used binder, including but not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, ethylene oxide-containing polymers, carboxylated polyvinyl chloride, polyvinyl pyrrolidone, polyurethane, polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0054] In some embodiments, the negative electrode composite lithium supplement material includes a lithium supplement frame and a negative electrode lithium supplement material, and the negative electrode lithium supplement material contains at least one of metallic lithium and a lithium alloy, and the lithium alloy includes at least one of a lithium aluminum alloy and a lithium indium alloy.
[0055] According to some embodiments of the present application, the positive electrode sheet is the positive electrode sheet according to the present application. According to some embodiments of the present application, the positive electrode active material layer comprises a positive electrode active material, a positive electrode composite lithium supplement material, a conductive material and a binder.
[0056] According to some embodiments of the present application, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer is composed of the 1st to Nth layers arranged in sequence in the thickness direction, N>1, and N is an integer, the 1st layer is adjacent to the positive electrode current collector, and the Nth layer is the layer farthest from the positive electrode current collector in the positive electrode active material layer, and there are the i-th layer and the i+1-th layer in the 1st to the N-th layers, 1≤i≤N-1, and i is an integer,
[0057] The i-th layer and the i+1-th layer contain positive electrode composite lithium supplement material, and based on the total weight of the i-th layer, the content of the positive electrode composite lithium supplement material in the i-th layer is C i Based on the total weight of the i+1th layer, the content of the positive electrode composite lithium supplement material in the i+1th layer is C i+1 , and among them
[0058] C i >C i+1 , and Ci-C i+1 <8%.
[0059] In some embodiments, the positive electrode active material includes, but is not limited to: lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese (NCM) ternary material, lithium nickel cobalt aluminum (NCA) ternary material, lithium iron phosphate (LiFePO4), lithium iron manganese phosphate (LiMn x Fe 1- x PO4) or lithium manganate (LiMn2O4).
[0060] In some embodiments, the positive electrode active material is Li[Ni 1-x-y Co x M y ]O2(M=Mn, Al, etc., such as lithium nickel cobalt manganese oxide Li[Ni 1-x-y Co x Mn y ]O2, 1-xy ≥ 0.5, lithium nickel cobalt aluminum oxide Li[Ni 1-x-y Co x Al y ]O2, 1-xy≥0.5).
[0061] In some embodiments, the positive electrode composite lithium supplement material includes a lithium supplement frame and a positive electrode lithium supplement material, and the positive electrode lithium supplement material includes at least one of lithium halide, lithium sulfide, lithium oxide, lithium peroxide, lithium nitride, and Li2C2.
[0062] In some embodiments, the binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector. In some embodiments, the binder includes: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin or nylon, etc.
[0063] In some embodiments, the conductive material includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0064] In an exemplary embodiment, Figure 1As shown in , N is 2, the active material layer is arranged on the current collector, and the active material layer is composed of a first layer and a second layer arranged in sequence in the thickness direction, wherein the first layer and the second layer contain a composite lithium supplement material, and based on the total weight of the first layer, the content of the composite lithium supplement material in the first layer is C1, based on the total weight of the second layer, the content of the composite lithium supplement material in the second layer is C2, and wherein
[0065] C1>C2, and C1-C2<8%.
[0066] In an exemplary embodiment, Figure 2 As shown in , N is 3, the active material layer is arranged on the current collector, and the active material layer is composed of a first layer, a second layer and a third layer arranged in sequence in the thickness direction, wherein the first layer and the second layer contain a composite lithium supplement material, and based on the total weight of the first layer, the content of the composite lithium supplement material in the first layer is C1, based on the total weight of the second layer, the content of the composite lithium supplement material in the second layer is C2, based on the total weight of the third layer, the content of the composite lithium supplement material in the third layer is C3, and wherein
[0067] C1>C2, and C1-C2<8%;
[0068] C2>C3, and C2-C3<8%.
[0069] The material and shape of the separator used in the embodiments of the present invention are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present invention.
[0070] For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene and polyethylene terephthalate. Specifically, polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film can be selected.
[0071] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0072] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0073] The polymer layer contains polymers, and the polymer material is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxide, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).
[0074] In some embodiments, the separator is a polyethylene (PE) separator coated with ceramic layers on both sides, wherein the PE layer thickness is in the range of 5 to 20 μm, and the coating thickness of each ceramic layer is in the range of 0 to 5 μm.
[0075] In some embodiments, the electrolyte includes a lithium salt and a solvent.
[0076] In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), or lithium difluorooxalatoborate.
[0077] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0078] In a preferred embodiment according to the present invention, the electrolyte is LiPF6 / EC+DMC+EMC.
[0079] The electrochemical device according to the present invention can be used in electronic devices, including but not limited to laptop computers, pen-type computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0080] Test Method
[0081] Energy density mean test
[0082] Place the battery cell in a 45℃ environment and let it stand for 3h. When the battery cell reaches 45℃, discharge it to 3V at 0.7C and let it stand for 30min. Charge it to the cutoff current at 0.7C constant voltage and let it stand for 30min. Repeat the above steps 3 times, and measure the discharge energy each time, and calculate the average value Eeverage of the 3 discharge energies E. Measure the mass M of the battery cell with a scale, and calculate the average mass energy density PED, PED=Eeverage / M.
[0083] Cycle capacity retention test
[0084] Place the battery cell in a 45℃ environment and let it stand for 3h. When the battery cell reaches 45℃, charge it to 4.3V at 1.5C, then charge it to 4.48V at 0.7C, then charge it at 4.48V at a constant voltage to a cutoff current of 0.05C, and then discharge it to 3V at 0.5C. Record the initial capacity Q1. When the cycle reaches the required number of times, take the previous discharge capacity as the battery capacity Q2, and calculate the capacity retention rate, capacity retention rate (%) = Q2 / Q1×100%.
[0085] Non-lithium charging capability boundary test
[0086] The battery is charged to 4.3V at 1.5C (or 2C, 1.3C, 1.2C or 1C), then charged to 4.48V at 0.7C, then charged to a cut-off current of 0.05C at 4.48V constant voltage, and then discharged to 3V at 0.5C for 20 times at 25°C (i.e. 1.5C step charging). The battery is fully charged and disassembled to observe the interface condition of the negative electrode. If the negative electrode is golden yellow, it is judged that there is no lithium precipitation, indicating that the negative electrode can support charging with this system (1.5C) at this temperature; on the contrary, if the negative electrode is partially or entirely gray, that is, lithium precipitation occurs, indicating that the negative electrode does not support charging with this system (1.5C).
[0087] Lithium stripping and insertion specific capacity test
[0088] The battery cell is charged and discharged at a rate of 0.2C, and the capacity of lithium removal and lithium insertion of the battery cell is recorded. The above capacity is divided by the mass of the active material to calculate the lithium removal & lithium insertion specific capacity.
[0089] Example 1
[0090] (1) Preparation of negative electrode sheet: negative electrode active material high energy density graphite, SiOx material, thickener sodium carboxymethyl cellulose (CMC-Na), binder PAA, binder styrene butadiene rubber, conductive agent conductive carbon black are mixed in a weight ratio of 82.8:14.6:0.6:0.6:0.6:0.8, deionized water is added, and negative electrode slurry is obtained under the action of a vacuum mixer; the negative electrode slurry is coated on a 5 μm thick copper foil by an extrusion coater, and then dried and cold pressed to obtain a negative electrode sheet;
[0091] (2) Preparation of positive electrode sheet: NCM811 material, PVDF, conductive carbon black, Li2O / carbon nanotube composite lithium supplement material are mixed in a mass ratio of 88.5%:1.4%:1.1%:9.0%, NMP (N-methylpyrrolidone) is added, and positive electrode slurry 1 is obtained under the action of a vacuum mixer to obtain a slurry with a solid content of 70% to 80% and a viscosity of 4000 to 7000 mPa·s. NCM811 material, PVDF, conductive carbon black, Li2O / carbon nanotube composite lithium supplement material are mixed in a mass ratio of 96.5%:1.4%:1.1%:1.0%, NMP (N-methylpyrrolidone) is added, and positive electrode slurry 2 is obtained under the action of a vacuum mixer to obtain a slurry with a solid content of 70% to 80% and a viscosity of 4000 to 7000 mPa·s. Then, the positive electrode slurries 1 and 2 are coated on the 10 μm thick aluminum foil using an extrusion double-layer coating machine in a double-layer coating manner, wherein slurry 1 is coated on the side close to the current collector to form the first layer, and slurry 2 is coated on the side away from the current collector to form the second layer, completing the coating process. Then, drying, cold pressing, slitting, and then drying and cold pressing are performed to obtain positive electrode sheets;
[0092] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) are mixed evenly, and then LiPF6 is added and mixed evenly to obtain an electrolyte; wherein the mass percentage of LiPF6 based on the mass of the electrolyte is 12%.
[0093] (4) Preparation of the diaphragm: A 2 μm thick ceramic coating was coated on both sides of a 7 μm thick polyethylene (PE) porous polymer film as a diaphragm.
[0094] (5) Battery assembly: The positive electrode sheets and the negative electrode sheets are stacked together with the separator to prepare a bare cell, which is placed in a packaging bag, and then injected and formed to obtain a lithium-ion battery.
[0095] Example 2-3
[0096] Embodiments 2 and 3 are carried out with reference to embodiment 1, except that different parameters are set according to Table 1.
[0097] Example 4
[0098] (1) Preparation of negative electrode sheet: negative electrode active material high energy density graphite, SiOx material, thickener sodium carboxymethyl cellulose (CMC-Na), binder PAA, binder styrene butadiene rubber, conductive agent conductive carbon black, Li metal / carbon nanotube composite lithium supplement material are mixed in a weight ratio of 79.5%: 13.9%: 0.6%: 0.6%: 0.6%: 0.8%: 4.0%, deionized water is added, and negative electrode slurry 1 is obtained under the action of a vacuum mixer to obtain a solid content of 40% to 49% and a viscosity of 3000 to 6500 mPa. ·s slurry; the negative electrode active material high energy density graphite, SiOx material, thickener sodium carboxymethyl cellulose (CMC-Na), binder PAA, binder styrene-butadiene rubber, conductive agent conductive carbon black, Li metal / carbon nanotube composite lithium supplement material are mixed according to a weight ratio of 81.1%: 14.3%: 0.6%: 0.6%: 0.6%: 0.8%: 2.0%, deionized water is added, and negative electrode slurry 2 is obtained under the action of a vacuum mixer; a slurry with a solid content of 40% to 49% and a viscosity of 3000 to 6500 mPa·s is obtained. Subsequently, the above-mentioned negative electrode slurries 1 and 2 are used to coat the slurry on a 5μm thick copper foil using an extrusion double-layer coater in a double-layer coating manner, wherein slurry 1 is coated on the side close to the current collector to form the first layer, and slurry 2 is coated on the side away from the current collector to form the second layer. Subsequently, drying, cold pressing, and striping are performed to complete the preparation of the negative electrode sheet;
[0099] (2) Preparation of positive electrode sheet: NCM811 material, PVDF, and conductive carbon black are mixed in a mass ratio of 97.5%:1.4%:1.1%, and NMP (N-methylpyrrolidone) is added to obtain positive electrode slurry under the action of a vacuum mixer to obtain a slurry with a solid content of 70% to 80% and a viscosity of 3500 to 6500 mPa·s. The slurry is coated on the above-mentioned 10μm thick aluminum foil using an extrusion coater in a normal coating manner to complete the coating process. Subsequently, drying, cold pressing, and slitting are completed to complete the preparation of positive electrode sheets;
[0100] (3) Preparation of electrolyte: In an argon atmosphere glove box with a water content of <10 ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) are mixed evenly, and then LiPF6 is added and mixed evenly to obtain an electrolyte; wherein the mass percentage of LiPF6 based on the mass of the electrolyte is 12%.
[0101] (4) Preparation of the diaphragm: A 2 μm thick ceramic coating was coated on both sides of a 7 μm thick polyethylene (PE) porous polymer film as a diaphragm.
[0102] (5) Battery assembly: The positive electrode sheets and the negative electrode sheets are stacked together with the separator to prepare a bare cell, which is placed in a packaging bag, and then injected and formed to obtain a lithium-ion battery.
[0103] Example 5
[0104] Example 5 is carried out with reference to Example 4, except that different parameters are set according to Table 1.
[0105] Embodiment 6-13
[0106] Examples 6-12 were carried out with reference to Example 1, except that different parameters were set according to Table 1.
[0107] Embodiment 14
[0108] Example 14 is carried out with reference to Example 1, except that the positive electrode sheet is obtained by the following steps:
[0109] NCM811 material, PVDF, conductive carbon black, Li2O / carbon nanotube composite lithium supplement material are mixed in a mass ratio of 90.5%: 1.4%: 1.1%: 7.0%, NMP (N-methylpyrrolidone) is added, and positive electrode slurry 1 is obtained under the action of a vacuum mixer. NCM811 material, PVDF, conductive carbon black, Li2O / carbon nanotube composite lithium supplement material are mixed in a mass ratio of 92.5%: 1.4%: 1.1%: 5.0%, NMP (N-methylpyrrolidone) is added, and positive electrode slurry 2 is obtained under the action of a vacuum mixer. NCM811 The material, PVDF, conductive carbon black, and Li2O / carbon nanotube composite lithium supplement material are mixed in a mass ratio of 94.5%:1.4%:1.1%:3.0%, and NMP (N-methylpyrrolidone) is added to obtain positive electrode slurry 3 under the action of a vacuum mixer. Then, the positive electrode slurries 1&2&3 are used to coat the slurries on the 10 μm thick aluminum foil using an extrusion multilayer coater in a three-layer coating manner, wherein slurry 1 is coated on the side close to the current collector to form the first layer, slurry 3 is coated on the side away from the current collector to form the third layer, and slurry 2 is coated between the first layer and the third layer to form the second layer. Then, the positive electrode sheet is dried and cold pressed.
[0110] Comparative Example 1
[0111] Comparative Example 1 is carried out with reference to Example 1, except that the positive electrode sheet is obtained by the following steps:
[0112] NCM811 material, PVDF and conductive carbon black are mixed in a mass ratio of 97.5%:1.4%:1.1%, NMP (N-methylpyrrolidone) is added, and positive electrode slurry is obtained under the action of a vacuum mixer. The positive electrode slurry is coated on the above-mentioned 10 μm thick aluminum foil through an extrusion coater, and then dried and cold pressed to obtain a positive electrode sheet.
[0113] Comparative Example 2
[0114] Comparative Example 1 is carried out with reference to Example 1, except that the positive electrode sheet is obtained by the following steps:
[0115] Take NCM811 material, PVDF, conductive carbon black, Li2O / carbon nanotube composite lithium supplement material according to the mass ratio of 92.5%:1.4%:1.1%:5.0%, add NMP (N-methylpyrrolidone), obtain positive electrode slurry under the action of vacuum mixer, obtain slurry with solid content of 70% to 80% and viscosity of 4000 to 7000 mPa·s, and apply the slurry to the above 10μm thick aluminum foil with an extrusion coater in a normal coating manner to complete the coating process. Then dry, cold press, and slit to complete the preparation of positive electrode sheet.
[0116] Comparative Example 3
[0117] Comparative Example 3 is carried out with reference to Example 4, except that the negative electrode sheet is obtained by the following steps:
[0118] The negative electrode active material high energy density graphite, SiOx material, thickener sodium carboxymethyl cellulose (CMC-Na), binder PAA, binder styrene butadiene rubber, conductive agent conductive carbon black, Li metal / carbon nanotube composite lithium supplement material are mixed in a weight ratio of 80.3:14.1:0.6:0.6:0.6:0.8:3.0, deionized water is added, and the negative electrode slurry is obtained under the action of a vacuum mixer; the slurry is coated on a 5μm thick copper foil by an extrusion coater to complete the coating process. Then it is dried, cold pressed, and slit to obtain the negative electrode sheet.
[0119] Comparative Examples 4-5
[0120] Comparative Examples 4-5 were carried out with reference to Example 1, except that different parameters were set according to Table 1.
[0121]
[0122]
[0123]
[0124] It can be seen from Table 1 that the lithium-ion batteries in the embodiments generally obtain improved capacity retention rates by means of the pole pieces according to the present invention. Since an active material layer of a composite lithium replenishing material having a gradient content is arranged on the current collector of the pole piece, the active material layer farther from the current collector contains a lower content of the composite lithium replenishing material. Therefore, during the lithium replenishment process, lithium can be released uniformly without being affected by the distance from the current collector, which significantly improves the cycle performance of the battery.
[0125] It can be seen from Comparative Example 4 that when the gradient formed by the content of the composite lithium supplementing material provided on the pole piece is too large, it will cause instability of the pole piece structure and lead to significantly deteriorated cycle performance.
[0126] Combining Comparative Example 2 and Examples 1-3 and 6-14, it can be seen that when a lithium-ion battery uses the positive electrode sheet according to the present invention, the lithium-ion batteries of Examples 1-3 and 6-14 achieve significant improvements in capacity retention or non-lithium precipitation charging capacity boundary, especially when the lithium-supplementing material and the composite lithium-supplementing material have a smaller particle size, a higher non-lithium precipitation charging capacity boundary can be obtained while improving the capacity retention rate, so that lithium-ion batteries can be used more efficiently under the premise of safety and stability.
[0127] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims, and these modifications and changes also fall within the scope of protection of the present invention.
Claims
1. A pole piece, characterized in that: The pole piece includes a current collector and an active material layer disposed on the current collector, wherein the active material layer is composed of a first layer to an Nth layer arranged in sequence in a thickness direction, N>1, and N is an integer, the first layer is adjacent to the current collector, and the Nth layer is the layer farthest from the current collector in the active material layer, and there are an i-th layer and an i+1-th layer in the first layer to the N-th layer, 1≤i≤N-1, and i is an integer, The i-th layer and the i+1-th layer contain a composite lithium supplement material, and based on the total weight of the i-th layer, the content of the composite lithium supplement material in the i-th layer is C i Based on the total weight of the i+1th layer, the content of the composite lithium supplement material in the i+1th layer is C i+1 , and among them C i >C i+1 , and C i -C i+1 <8%.
2. The pole piece according to claim 1, characterized in that: The composite lithium supplement material comprises a lithium supplement frame and a lithium supplement material.
3. The pole piece according to claim 2, characterized in that: The lithium supplement framework includes at least one of the following: porous carbon, carbon nanotubes, carbon fibers, graphene, metal-organic framework compounds (MOFs), SnO2, ZnO, indium-doped tin oxide (ITO), antimony-doped tin oxide (ATO), and ruthenium oxide.
4. The pole piece according to claim 1, characterized in that: The pole piece is a positive pole piece, the current collector is a positive current collector, and the active material layer is a positive active material layer, and wherein, The composite lithium supplement material includes a lithium supplement frame and a positive electrode lithium supplement material, and the positive electrode lithium supplement material includes at least one of lithium halide, lithium sulfide, lithium oxide, lithium peroxide, lithium nitride, and Li2C2.
5. The pole piece according to claim 1, characterized in that: The electrode sheet is a negative electrode sheet, the current collector is a negative electrode current collector, and the active material layer is a negative electrode active material layer, and wherein, The composite lithium supplement material includes a lithium supplement frame and a negative electrode lithium supplement material, and the negative electrode lithium supplement material contains at least one of metallic lithium and a lithium alloy, and the lithium alloy includes at least one of a lithium aluminum alloy and a lithium indium alloy.
6. The pole piece according to claim 1, characterized in that: The porosity of the composite lithium supplement material is 20% to 70%, preferably 30% to 50%.
7. The pole piece according to claim 1, characterized in that: The average particle size D1 of the composite lithium supplement material is 20 nm-20 μm, preferably 100 nm-10 μm.
8. The pole piece according to claim 1, characterized in that: Based on the total weight of the Nth layer, the content of the composite lithium supplement material in the Nth layer is C N , and 0.5 wt% ≤ C N <C i ≤10 wt%, preferably 2 wt%≤C N <C i ≤5% by weight.
9. The pole piece according to claim 1, characterized in that: When i is any integer from 1 to N-1, it satisfies: 3.5×C i+1 >C i >C i+1 , preferably 2.5×C i+1 >C i >1.2×C i+1 .
10. The pole piece according to claim 1, characterized in that: There are an i-th layer and a j-th layer in the first layer to the N-th layer, 1≤i≤N-1, 1≤j≤N-1, i and j are both integers and i≠j, and based on the total weight of the j-th layer, the content of the composite lithium supplement material in the j-th layer is C j , and among them, |C i -C j |≤(|ij| / (N-1))*6%.
11. The pole piece according to claim 2, characterized in that: The average particle size D2 of the lithium supplement material is 1 nm-1 μm, preferably 5 nm-0.5 μm.
12. The pole piece according to claim 2, characterized in that: The average particle size D1 of the composite lithium supplement material and the average particle size D2 of the lithium supplement material satisfy: 5≤D1 / D2≤50, preferably 10≤D1 / D2≤20.
13. The pole piece according to claim 2, characterized in that: Based on the weight of the composite lithium-supplementing material, the content of the lithium-supplementing material is 45 wt % to 85 wt %, preferably 60 wt % to 75 wt %.
14. An electrochemical device, characterized in that: The electrochemical device comprises a pole piece according to any one of claims 1 to 13.